2017
DOI: 10.1080/03079457.2017.1339346
|View full text |Cite
|
Sign up to set email alerts
|

Evidence and role of phlebitis and lipid infiltration in the onset and pathogenesis of Wooden Breast Disease in modern broiler chickens

Abstract: Wooden Breast Disease (WBD), a myopathy that frequently affects modern broiler chickens, is a disorder that has been associated with significant economic losses in the poultry industry. To examine tissue changes associated with the onset and early pathogenesis of this disorder, a time-series experiment was conducted using chickens from a high-breast-muscle-yield, purebred commercial broiler line. Birds were raised for up to seven weeks, with a subset of birds sampled weekly. Breast muscle tissues were extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
146
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(176 citation statements)
references
References 66 publications
(111 reference statements)
28
146
0
2
Order By: Relevance
“…Several studies have been conducted to ascertain the possible factors involved in the occurrence of WS, WB, and SM in fast‐growing broilers (Table ). It is widely accepted that the incidence of breast abnormalities rises with increasing slaughter weight (Cruz et al., ; Lorenzi et al., ; Papah et al., ), growth rate (Kuttappan et al., , , ; Lorenzi et al., ), and genetic potential for breast meat yield (Alnahhas et al., ; Bailey et al., ; Livingston et al., ; Lorenzi et al., ; Petracci et al., ; Trocino et al., ) in agreement with strong genetic correlations found by Alnahhas et al. ().…”
Section: Means Of Alleviation: Facts and Challengesmentioning
confidence: 52%
See 4 more Smart Citations
“…Several studies have been conducted to ascertain the possible factors involved in the occurrence of WS, WB, and SM in fast‐growing broilers (Table ). It is widely accepted that the incidence of breast abnormalities rises with increasing slaughter weight (Cruz et al., ; Lorenzi et al., ; Papah et al., ), growth rate (Kuttappan et al., , , ; Lorenzi et al., ), and genetic potential for breast meat yield (Alnahhas et al., ; Bailey et al., ; Livingston et al., ; Lorenzi et al., ; Petracci et al., ; Trocino et al., ) in agreement with strong genetic correlations found by Alnahhas et al. ().…”
Section: Means Of Alleviation: Facts and Challengesmentioning
confidence: 52%
“…(). This has been also confirmed by histological observations which evidenced that myodegeneration progress associated with the development of breast abnormalities is strictly related to age at slaughter (Griffin et al., ; Kawasaki et al., ; Papah et al., ; Radaelli et al., ; Sihvo et al., ) and breast growth pattern (Papah et al., ) (Table ; Radaelli et al., ). Recently, it was also demonstrated that egg storage duration before hatching as well as manipulation of embryonic development by egg incubation temperatures and chick weight at hatching can affect muscle morphology traits and related to occurrence of breast abnormalities (Clark, Walter, & Velleman, ; Livingston et al., ).…”
Section: Means Of Alleviation: Facts and Challengesmentioning
confidence: 67%
See 3 more Smart Citations